Using Arterial Pressure Index to Predict Arterial Injuries in Penetrating Trauma to the Upper Extremities. Issue 1 (January 2023) - Tung, Lily; Seamon, Mark J.; Dauer, Elizabeth; Alabi, Olamide; Benarroch‐Gampel, Jaime; Passman, Jesse; Fitzgerald, Caitlin; Lobichusky, Brone; Mazzei, Michael; Rodriguez, Wendy; Smith, Randi N.
Background: Upper extremity (UE) vascular injuries account for 18.4% of all traumatic vascular injuries. Arterial pressure index (API) use in lower extremity injuries to determine the need for further investigations is well established. However, due to collateral circulation in UEs, it is unclear if the same algorithm can be applied. The purpose of this study was to determine if APIs can be used to determine the need for computed tomography angiogram (CTA) in penetrating UE trauma. Methods: All adult trauma patients with penetrating UE trauma and APIs from 2006 to 2016 were identified at 3 urban US level 1 trauma centers. Sensitivity, specificity, and positive and negative predictive values of APIs <.9 in detecting UE arterial injuries were calculated. Results: During the 11-year study period, 218 patients met our inclusion criteria. Gunshot wounds comprised 76.6% and stab wounds 17.9%. Median injury severity score and API were 9 and 1, respectively. Seventy-two of our patients underwent evaluation with CTA. Of the injuries, the most common were thrombus or occlusion (46.7%), transection (23.1%), and dissection (15.4%), radiographically. Ultimately, 32 patients underwent surgical.